Misperception of the benefits and working mechanism of the National Health Protection in the District of Sumba Timur, Indonesia - Asnani; Windi, Yohanes Kambaru; Harnani, Baiq Dewi (PT Inovasi Pratama Internasional, 2024)
The National Health Insurance (NHI) of Indonesia covers the health care of nearly the whole population of Indonesia. However, misunderstandings of the benefits and the healthcare access mechanism are still evident. The study aims to identify misperceptions regarding the benefits and working mechanisms of the NHI in Waingapu, Sumba Timur District, Indonesia. A qualitative inquiry identifies the misperception about NHI's benefits and working mechanism. Thirty residents were recruited using the consecutive procedure to participate in the study. The data collections are semi-structured interviews, casual conversations, and inductively analyzed. The qualitative analysis identifies that people perceive that the administrative procedure of health care under NHI is complicated, has unlimited drugs and health care coverage, and the premium contribution is claimable. People perceive the management of NHI to treat them as debtors when they delay paying their contributions. People feel they are being treated unfairly because NHI does not provide all health services, but they ask for a guarantee if NHI does not cover health services. It is concluded that the people are underinformed about NHI's benefits and working mechanism. The management of NHI and associated stakeholders should implement ongoing educational programs and promotional efforts to increase awareness and understanding of the NHI system.